Health-Related Quality of Life in Mandarin-Speaking Children With Cochlear Implants. Issue 3 (May 2019) - Zhao, Yawen; Li, Ying; Zheng, Zhipeng; Li, Jing; Nie, Xiaolu; Jin, Xin; Zheng, Jun; Zhang, Jie; Chen, Min; Hao, Jinsheng; Yang, Yang; Liu, Wei; et al.
Abstract : Objectives: The primary aim of this study was to evaluate the health-related quality of life (HRQoL) of children with cochlear implants (CIs) from the parental perspective. The secondary objective was to explore possible relationships between demographic variables (such as age at assessment, gender, age at implantation, and duration of language rehabilitation) and the HRQoL. The third objective was to determine the developmental trajectories of HRQoL. Design: This study included parents of 123 children with CIs (mean age, 40.45 months; mean age of CI implantation, 24.74 months; mean device experience, 16.34 months). The time periods for follow-up were at 0, 1, 2, 3, 6, and 12-month intervals of CI use. The Mandarin Children with Cochlear Implants: Parental Perspectives questionnaire was employed to assess HRQoL. Results: Parents were satisfied with HRQoL, especially with the domain of social relations; however, education received a less positive rating. The duration of CI use was positively correlated with 5 domains, suggesting that children who used CIs for a longer time had higher HRQoL ratings. Children with longer language rehabilitation received more positive ratings in the domains of social relations and education ( p < 0.05); children whose mothers had higher education levels received more positive ratings in the domain of general functioning ( p < 0.05); children living in cities received more positive ratings in the domains of communication, general functioning and self-reliance ( p < 0.05). Girls received more positive rating than boys in the domain of well-being ( p < 0.05). No significant correlation was found between age at implantation, age at assessment, only child status, and HRQoL. All domains showed clear increases in the duration of CI use; the majority of the domains showed steeper progress over the first 3 months of CI use. Communication exhibited the most rapid progress, with education progressing at a slower rate. Conclusions: Parents were satisfied with all domains of HRQoL. Almost all domains exhibited rapid progress over the first 3 months of CI use, with education progressing at a slower rate. This research underscores the importance of language rehabilitation by revealing that strengthening language rehabilitation could be an effective means of improving the HRQoL of children with CIs. Abstract : Supplemental Digital Content is available in the text.